Personal initiative and work environment as predictors of job satisfaction among nurses: cross-sectional study - Ilya Kagan; Tova Hendel; Bella Savitsky (BMC, 2021)
Abstract Background Job satisfaction contributes to better work outcomes and productivity, and reduces nurses' absenteeism and turnover. The contribution of personal initiative to the interaction between these variables needs additional examination. This study aimed to examine the relationships between personal initiative, work environment, and job satisfaction among nurses. Methods This was a cross-sectional study. The convenience sample consisted of 1040 nurses working in hospitals across the country. Data were collected by a structured self-administered questionnaire measuring: (a) personal initiative, (b) nursing work environment, (c) job satisfaction. Results Personal initiative and work environment scores, together with demographic and occupational characteristics that univariate analysis showed to be significantly associated with job satisfaction, were included in a logistic regression model to predict job satisfaction. The results of multivariable analysis indicated that female gender, working in emergency room (ER) and pediatric wards, a higher personal initiative, and positive perception of work environment, were significantly associated with higher job satisfaction. Work in the ER and pediatric area of practice was significantly associated with five-fold (OR = 4.97; 95% CI 1.52-16.25) and three-fold higher odds (OR = 2.85; 95% CI 1.17-6.91) for high and very high job satisfaction in comparison with work in oncology. The model explained 32% of the variance in job satisfaction. Conclusions The findings demonstrate that high personal initiative together with positive perceptions of the nursing work environment, contributed significantly to the explanation of job satisfaction. There is a need to invest more efforts in strengthening the organizational climate stimulating initiative behavior and encouraging nurses to be active, share knowledge, and promote innovation.